2021
DOI: 10.26633/rpsp.2021.130
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and inequities in the Americas: lessons learned and implications for essential health services

Abstract: The COVID-19 pandemic has exacerbated social, economic, and health-related disparities, which disproportionately affect persons living in conditions of vulnerability. Such populations include ethnic groups who face discrimination and experience barriers to accessing comprehensive health care. The COVID-19 pandemic has exposed these health disparities, and disruptions of essential health services have further widened the gaps in access to health care. Noncommunicable diseases are more prevalent among groups mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
5

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 15 publications
0
17
0
5
Order By: Relevance
“…Previous studies have shown that certain traits of poor countries have a direct impact on COVID-19 outcomes. This includes low socioeconomic status, overcrowding, higher use of public transportation, absence of potable water, and informal work ( 7 ). As a result of the worst scenarios experimented on by infected adults, healthcare services, including pediatric ones, were rearranged to meet the increasing requirements of that age group ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that certain traits of poor countries have a direct impact on COVID-19 outcomes. This includes low socioeconomic status, overcrowding, higher use of public transportation, absence of potable water, and informal work ( 7 ). As a result of the worst scenarios experimented on by infected adults, healthcare services, including pediatric ones, were rearranged to meet the increasing requirements of that age group ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has exacerbated pre-existing socioeconomic and health disparities worldwide [ 30 ] which, in turn, increase the risk of SARS-CoV-2 infection and COVID-19 morbidity in children. This is due to poverty-related comorbidities (e.g., malnutrition), reduced access to healthcare, low-quality and overcrowded housing, and parents′ exposure to high-risk occupations [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A medida que la vacunación contra la COVID-19 crea la oportunidad de superar la pandemia ( 19 ), el avance en el proceso de vacunación en todos los países del continente ha sido un aliciente entre la población, ya que provee de esperanzas a retornar a la normalidad. Además, acerca a la meta de lograr la inmunidad de rebaño contra la COVID-19, la cual según la OMS se logra cuando 70% de la población es inmune ( 20 ).…”
Section: Discussionunclassified